2020
DOI: 10.1177/1359105320962268
|View full text |Cite
|
Sign up to set email alerts
|

How is obesity associated with happiness? Evidence from China

Abstract: Happiness is a universal goal that people pursue. Studies of the relationship between obesity and happiness have shown mixed findings. It is uncertain whether an optimum BMI level exists and at what level obesity interferes or interacts with happiness. Guided by the Circle of Discontent Theory, we examined the relationship between obesity and happiness among Chinese residents using the 2014 China Family Panel Studies data. The results reveal an inverted U-shaped relationship between BMI and happiness, with obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The fact was consistent with past studies in adults [46,47] which signi cantly lower levels of happiness were reported in the obesity group. In general, people with high BMI generally experience greater social stress which had required that have to be thin, especially for women [48,49].…”
Section: Discussionsupporting
confidence: 93%
“…The fact was consistent with past studies in adults [46,47] which signi cantly lower levels of happiness were reported in the obesity group. In general, people with high BMI generally experience greater social stress which had required that have to be thin, especially for women [48,49].…”
Section: Discussionsupporting
confidence: 93%
“…Yet all these studies, while acknowledging the existence of obesity’s intangible costs, make no attempt to quantify them, focusing only on the direct and indirect expenses. This failure is surprising not only because of the widely documented obesity-SWB link [ 18 20 ] and obesity stigmatization [ 51 ], but because a long tradition of intangible cost estimation in several economics field (e.g., transport, environmental, and public economics) has furnished a viable, but as yet unused, method for measuring obesity’s intangible costs.…”
Section: Discussionmentioning
confidence: 99%
“…Nor does it capture any of the loss of well-being caused by discrimination or bullying. This research void is rather surprising given not only the potential economic significance of such intangible costs but also obesity’s well-documented negative effects on SWB [ 18 20 ], often through stigmatization and discrimination [ 21 ]. For example, in the US, obese individuals earn about 10% less than their healthy weight counterparts even with productivity controlled for [ 22 ] and may even be blatantly dehumanized [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the prevalence of e‐commerce, more and more marketing scholars are beginning to study hedonic consumption and utilitarian consumption behavior in the online shopping context. Previous studies have found that hedonic and utilitarian value, as important motivations for the online retail shopping behavior of consumers (Bridges & Florsheim, 2008; To et al, 2007), play a significant role in promoting online group buying intention (e.g., Lim, 2014; Lim, 2017), overall satisfaction (e.g., Liu, Xu, & Hagedorn, 2022), and attitudes toward promotion and behavioral intention (e.g., Jee, 2021). Referring to the above research, we focus on the key role of the proportion of consumers' spending on hedonic and utilitarian goods between online shopping and consumer SWB for the following reasons.…”
Section: Literature Reviewmentioning
confidence: 99%